Supplementing aerial drone surveys with biotelemetry data validates wildlife detection probabilities - Hvala, Aliesha; Rogers, Rebecca M.; Alazab, Mamoun; Campbell, Hamish A. (Frontiers in Conservation Science, 2023)
Aerial drone systems are now widely used to survey wildlife, but variation in the detectability of individuals is rarely assessed. This is a critical shortfall because wildlife detectability from the air is likely to be influenced by the local environment. In this study, we integrated Animal Biotelemetry technology with aerial drone systems to assess the temporal and environmental factors influencing animal detection probability and, thus, total counts. Wild-caught feral pigs (Sus scrofa) were fitted with GPS tracking collars and released into a large natural habitat enclosure in northern Australia. A fixed-wing drone equipped with a dual camera (thermal infrared and RGB) was repeatedly flown over the study area between sunrise and sunset in the wet and dry seasons. The study found that the probability that a pig was visible in aerial imagery was highly variable depending on the timing of the aerial survey. The lowest detection probability was mid-afternoon (5 to 20 %), and the highest was early evening (50 to 75%). There was seasonal variation in detection probability, and in the wet season, detection probability in the mornings remained greater than 50%, but in the dry was less than 30 %. Temporal trends in detection probability were similar in thermal infrared and RGB imagery. The GPS location data enabled us to assess how animals interacted with localised factors (canopy cover, land cover, ambient temperature) to influence detection probability. This enabled the selection of survey times to maximize feral pig detection and the development of a correction factor to account for non-detected individuals at specific times and locations. The study demonstrates the value of integrating Animal Biotelemetry and aerial drone systems to account for variations in detection probability when undertaking wildlife aerial surveys.